2019
DOI: 10.3329/ijarit.v9i1.42943
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors influencing poverty among rural households in onicha local government area, ebonyi state, Nigeria

Abstract: The study examined the socio-economic factors influencing poverty among rural households in Onicha Local Government Area of Ebonyi state, Nigeria. The study adopted multistage random and purposive sampling techniques to select 120 household heads. Primary data used for the study were collected using structured questionnaire. The data were analysed with the aid of means, percentage and frequency count and OLS multiple regression model. The result indicated that the households spent an average of N31,250 monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Therefore, they can make positive contribution to agricultural development. This finding is in line with [20]. Table 1 reveals that the average households' size were 6 members in the Ebonyi rice farmers households, implying that majority of them have relatively high household sizes.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, they can make positive contribution to agricultural development. This finding is in line with [20]. Table 1 reveals that the average households' size were 6 members in the Ebonyi rice farmers households, implying that majority of them have relatively high household sizes.…”
Section: Resultssupporting
confidence: 81%
“…Fifty-six percent of the population lives below US $1 per day (GDP) with limited social service and infrastructure, high levels of unemployment and underemployment, and with very few industries with a low output. (Eze et al, 2019;National Bureau of Statistics, 2019;Olawuyi & Adetunji, 2013). Moreover the world bank stated that Nigeria had overtaken India as the country with the highest number of impoverished individuals (Babalola, 2018).…”
Section: All the 13mentioning
confidence: 99%
“…For instance, Uzochukwu et al (2008) reported that many rural households in Nigeria might not pay for all their drugs and treatments. Although the cost of YF vaccination may be affordable, the prevailing economic crisis and abject poverty could hinder rural households from seeking appropriate healthcare (Eze et al, 2019).…”
Section: Izzimentioning
confidence: 99%
“…Tersoo (2013) viewed poverty as a state where an individual is not able to cater for his or her basic needs of food, clothing and shelter. Poverty manifests itself in lack of income and productive resources, low purchasing power, low life expectancy, malnutrition, lack of access to social and economic services (Adebayo, 2013;Eze, Odoh, Igwe and Mgbanya, 2019). Poverty is considered as a major menace in the Nigerian society.…”
Section: Introductionmentioning
confidence: 99%
“…The poverty rate in the State was 56% which was higher than the national average of 46% and average of 27% for the South East in 2013 (UNDP, 2013). Recently, the poverty rate in Ebonyi State increased to 58.9% (Eze et al, 2019). About 80% of Ebonyi citizens are classified as falling below the poverty line, which is, living below the $1.9 per day benchmark with life expectancy of 47 years (UNDP, 2013;UNDP 2016;NBS, 2017).…”
Section: Introductionmentioning
confidence: 99%